(untitled) (Research, Society and Development, 2020)
Objetctive: understand the perception of quilombola women about prenatal care received during pregnancy. Methodology: This is a qualitative, descriptive study, carried out in September 2017 in a rural community of quilombola remnants, located in a municipality in Northeastern, Brazil. Participated in the all woman who were pregnant between 2014 and July 2017. Data were collected through semi-structured interviews and analyzed using Content Analysis. Results: It was possible to show that quilombola women understand prenatal care as an important resource to minimize pregnancy problems for both the mother and the newborn. In this context, it was noted that the nursing professional has a fundamental role in prenatal care and his performance goes beyond technical care, identified through the relationship of bond, support, trust and reception. In addition, the participants highlighted that despite the improvement in access to consultations with the implementation of a Family Health Strategy, there are still difficulties with regard to carrying out routine tests requested, since all depend exclusively on SUS. Conclusion: there is a need to strengthen the National Policy for Comprehensive Health of the Black Population and the National Policy for Comprehensive Care for Women’s Health, with a view to ensuring greater access to services and reducing inequities in health, since it is a group in a situation of double vulnerability, both for being a woman and for being black.